Synthesis and photo-catalytic degradation property of nanostructured-ZnO with different morphology - Wang, Y.; Li, Xin Yong; Lu, G.; Chen, G.; Chen, Y. (Elsevier BV, 2008)
ZnO nanostructures with different morphology have been successfully fabricated by a simple relative low temperature approach at 90 °C for 5 h without surfactant assistance. These structures can be easily tailed using varied concentrations of sodium hydroxide (NaOH) and different amounts of the hydrazine hydrate (N 2H 4·H 2O). X-ray diffraction (XRD) result proves the formation of ZnO with wurtzite structure. Microstructure as revealed by scanning electron microscopy (SEM) and transmission electron microscopy (TEM) indicates that the rod-like and chrysanthemum-like ZnO nanostructures contain many radial nanorods, which grow along the [0001] direction. Furthermore, the as-prepared ZnO nanomaterials exhibit high activity on the photo-catalytic degradation of typical persistent organic pollutants (POPs), indicating that they are promising as semiconductor photo-catalysts. © 2007 Elsevier B.V. All rights reserved.